Increase Interest in Learning Mathematics for 5th Grade Students Using Android Game-Based Learning Media - Wulan Ningdyah Anggraini (International Journal of Elementary Education, 2023)
This research article is based on observational data that indicates students' learning styles, frequently used instructional media, low math scores of 5th grade students, and students' inability to comprehend the taught materials. The objective of this research is to analyze students' learning interest in mathematics subjects using game-based educational media. The study was conducted in a 5th grade class with a total of 26 students. The research method used was Research and Development (R&D), and the development model employed was the ADDIE development model. The game product was tested by experts and students to assess the validity of the educational game. The results from expert evaluations yielded 92% for subject matter expertise, 94.67% for instructional design expertise, 94.44% for instructional media expertise, 100% for individual testing, and 92.92% for small group testing. The research involved 26 respondents who were 5th grade students in a primary school. The effectiveness test results showed a significant difference between the math scores of 5th grade students before and after using game-based Android instructional media. It can be concluded that game-based Android instructional media can enhance students' learning interest in 5th grade mathematics subjects at the primary school level.